2014
DOI: 10.1123/jsm.2013-0258
|View full text |Cite
|
Sign up to set email alerts
|

What Little Do We Know: Content Analysis of Disability Sport in Sport Management Literature

Abstract: As the field of sport business management develops, it is critical to assess its literature. A content analysis of 34 sport business management journals between 2002 to 2012 was conducted relative to sports, physical activity, recreation, and leisure for individuals with disabilities. Journals were selected based on their alignment with sport management curriculum standards. Results show that of the 5,443 articles reviewed in this study, merely 89, or .016%, pertained to disability sport, leisure, recreation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 14 publications
(30 reference statements)
0
27
0
2
Order By: Relevance
“…Mindent egybe véve, összesen 122 szerző működött közre a 116 cikk elkészítésében, közülük 62,3% volt féri és 37,3% nő. Ez rendkívül hasonló a nemzetközi eredményekhez (Shapiro & Pitts, 2014), ahol ez az arány 61% férfi és 36% nő (3%-ról a név alapján ez nem volt eldönthető).…”
Section: áBra a Kutatásba Vont Sportgazdasági Cikkek Száma 2003 éS 20unclassified
“…Mindent egybe véve, összesen 122 szerző működött közre a 116 cikk elkészítésében, közülük 62,3% volt féri és 37,3% nő. Ez rendkívül hasonló a nemzetközi eredményekhez (Shapiro & Pitts, 2014), ahol ez az arány 61% férfi és 36% nő (3%-ról a név alapján ez nem volt eldönthető).…”
Section: áBra a Kutatásba Vont Sportgazdasági Cikkek Száma 2003 éS 20unclassified
“…To start with, it is relevant to acknowledge the work of Shapiro and Pitts (2014) who after examining disability sport in sport management literature between 2002 to 2012 remark that research on disability sport, leisure and recreation is still an under research area in sport management. To further this argument, both authors state that out of 5,443 articles examined, only 89, less than 1 per cent were disability sport articles (see also Pitts and Shapiro 2017).…”
Section: Understanding Disability Elite Disability Sport and Human Rmentioning
confidence: 99%
“…In this regard, the World Leisure Journal was (and still is) one of the journals that has published more articles in this subject (Veal 2015). To date, most of the extant research on sport and leisure disability has focused upon the level of sport participation and the range of activities involving PwD (Patterson and Pegg 2009;Pitts and Shapiro 2017;Shapiro and Pitts 2014;Thomas and Smith 2009), and more recently on the analysis of another growing demographic group as old PwD (Sotiriadou and Wicker 2014). Shapiro and Pitts (2014: 663) found that 'nearly half (48%) of all papers addressing disability sport focused on "participant sport", followed by Paralympics (15.7%)'.…”
Section: Understanding Disability Elite Disability Sport and Human Rmentioning
confidence: 99%
See 2 more Smart Citations